BEBERAPA KARAKTERISTIK BARU PADA FUNGSI TERDEKATI - Abdul Aziz; Y.D. Sumanto; Solikhin Solikhin; Roberus Heri Utomo (Diponegoro University, 2019)
In this paper, discuss the relationship between approachable function with bounded variations, measurement, and absolute continuity. Futhermore, If f is approachable function of interval [a, b] then f is a bounded variation function and f is a measurable function of interval [a, b]. In relation with absolute continuity, if f is an absolute continuous of interval [a, b] then f is approachable function of [a, b].